Onkel-Toms-Hütte i Am Fischtal settlements in Berlin, as a reflection of the relation between avant-garde nad continuation trends in German architecture of the twenties of the XXth century in the field of housing - Hubert Trammer (Budownictwo i Architektura, 2011)
Onkel-Toms-Hütte i Am Fischtal settlements had been built side by side in Berlin in the twenties of the twentieth century. Together they create the example of the coexistence of the avant-garde and continuation tendencies in architecture. The shape of the settlements and their architecture show both the differences in the opinions of their authors, mainly concerning using flat or steeped roofs, as well as influences coming in both directions. Both settlements create interesting reference in many fields. Especially interesting is the way of incorporation of green into the space of settlements and the relation between public and private space. The Onkel-Toms-Hütte is an interesting example of placing shopping in the settlement.